Decisions of the Supreme Court of Newfoundland : the reports, 1941-1946 - Newfoundland. Supreme Court (D. R. Thistle, Queen's Printer, 1956)
The decisions of the Supreme Court of Newfoundland and Labrador. Most volumes include both case and topical indexes. Alternative title from spine. Missing pages:294-5, xiii-xiv.